IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Zuheir Ashraf Zakaria - Zakaria, Zuheir Ashraf (2015)
Article on: Article 1 - “Audio-visual piracy: towards a study of the underground networks of cultural globalization” Article 2 - “Audiovisual Piracy, Informal Economy, and Cultural Globalization”